Іnteraction between a tubular beam of charged particles and an anisotropic dispersive solid-state cylinder - Averkov, Yu.O.; Prokopenko, Yu.V.; Yakovenko, V.M. (Вопросы атомной науки и техники, 2018)
The interaction between a tubular beam of charged particles and a nonmagnetic anisotropic dispersive medium
of cylindrical configuration has been investigated. It has been found the absolute instability of bulk-surface waves
that occurs because of peculiarities of the anisotropic cylinder properties. The resonance behavior of the permittivity
frequency dependence causes the emergence of the sections of dispersion curves of the E-type bulk-surface
eigenmodes with negative group velocity. It has been shown there are the E-type surface eigenmodes and pseudo
surface eigenmodes of E- and H-types in the cylinder. Вивчено взаємодію нерелятивістського трубчастого потоку заряджених частинок з немагнітним анізотропним диспергуючим середовищем циліндричної конфігурації. Виявлена абсолютна нестійкість об'ємноповерхневих хвиль, що обумовлена особливостями властивостей анізотропного циліндра. Резонансний характер частотних залежностей діелектричної проникності циліндра призводить до появи ділянок дисперсійних кривих власних об'ємно-поверхневих хвиль E-типу з негативною груповою швидкістю. Показано існування в циліндрі власних поверхневих хвиль E-типу і псевдоповерхневих хвиль E- та H-типів. Изучено взаимодействие нерелятивистского трубчатого потока заряженных частиц с немагнитной анизотропной диспергирующей средой цилиндрической конфигурации. Обнаружена абсолютная неустойчивость
объёмно-поверхностных волн, обусловленная особенностями свойств анизотропного цилиндра. Резонансный характер частотных зависимостей диэлектрической проницаемости цилиндра приводит к появлению
участков дисперсионных кривых собственных объёмно-поверхностных волн E-типа с отрицательной групповой скоростью. Показано существование в цилиндре собственных поверхностных волн E-типа и псевдоповерхностных волн E- и H-типов.